Screening of the factors for hydrogel synthesis using design-of-experiment - Ab. Hadi, Hazrina; Abdul. Jalil, Mohd. Azri; Kasmuri, Abdul Razak (2016)
The two level factorial design was chosen from design experiment software version 8 (DOE 8, Minnesota, USA) to screen which factor could influence the response. For hydrogel mixture, polyvinyl alcohol (PVA) and polyethylene glycol (PEG) were used. 10% PVA was mixed with 1% PEG (v/v) together with 1% protein-free agar solution (w/v), 2% dextran (w/v) and 6% honey (v/v). For the PVA aqueous solution, 100g PVA was dissolved in 600mL distilled water for an hour until the solution was clear. 10g of agar was dissolved in 330mL distilled water and heated for about one hour until clear. Then, 20g dextran was dissolved in the mixture. The solution was stirred continuously before 10mL of PEG was added to create agar solution. After that, the mixture of PVA aqueous solution and agar solution were submerged in the ultrasonic water bath at 37°C for an hour and half for degassing purpose. When the temperature reached 45°C, 60mL of honey was added. For a control hydrogel, similar mixture was prepared with the exclusion of honey. They were frozen at −20°C for 18 h and then thawed at 25°C for 6 h to complete a cycle (F-T cycle). They were group to first cycle until third cycle. From the formulation lists, three response (swelling ratio, water vapor transmission and gel fraction) were chosen to study the influence of the factors selected towards the formulations. For the swelling ratio (Y1) response, the most significant (p<0.05) factors were honey concentration (X1), agar concentration (X2) and number of cycles (X3). It indicated that these three factors could influence the swelling ratio response whereas the dextran concentration unable to influence the swelling ratio swelling ratio (Y1) response. A higher value of water vapor transmission rate could cause the wound to dry quickly and eventually produced scar. Whereas, a lower water vapor transmission rate may hinder the healing process due to the accumulating exudates. The acceptable value for water vapor transmission rate are 2000-25000 gm -2 day -1. For the gel fraction percentage, the higher percentage of gel fraction indicated a higher strength of the gel, but the flexibility was decreased. As a conclusion, from this screening tests, three factors which are honey concentration (X1), Agar concentration (X2), number of cycles (X3) showed significant values on the selected response. Based on these results, the optimization test will be conducted to generate the best formulation for hydrogel.